The Effect of Audit Quality on Earnings Management: Evidence from China - Zhang, Mengzhe (2020)
Abstract The purpose of this study is to investigate whether audit quality is significantly associated with accrual earnings management (AEM) and real earnings management (REM) in China. Three proxies for audit quality including audit firm size, industry specialisation and audit tenure are used to examine the association based on a sample of 1164 observations in the Chinese manufacturing industry for the period 2015-2017. Modified Jones (1991) model is applied to measure discretionary accruals as a proxy of AEM while abnormal cash flows, abnormal production costs, and abnormal discretionary expenses are used separately and collectively to examine the amount of REM. The results of this research indicate that audit firm size has a significant relationship with REM while has an insignificant relationship with AEM. Industry specialisation and audit tenure are negatively related to AEM while positively related to REM. On the whole, higher audit quality impedes firms’ usage of AEM to some extent. In order to attain earnings targets, firms tend to resort to REM though harmful to long-term firm value, which also suggests a complementary relationship between AEM and REM. The findings further alert regulators that even though higher levels of audit quality in most cases constrains AEM to some extent, it might lead to even worse results of an increase in REM. Thus, policy-makers need to trade off the benefits and potential risks between AEM and REM brought by high audit quality when audit rules are promulgated or adjusted.